PREFERENSI NASABAH DALAM KEGIATAN FUNDING DI PT BPRS LANTABUR TEBUIRENG JOMBANG - Ismail Wardhono, Taufiq; Chamim, M (Irtifaq, 2021)
This study aims to analyze customer preferences in funding activities at PT BPRS Lantabur Tebuireng, analyzes funding activities, analyzes the factors of customer preference. There are two sources of data in this study, namely primary data sources and secondary data sources. After collecting data, writer used descriptive method to analyze. Funding activities carried out by PT BPRS Lantabur Tebuireng uses the ball pick-up technique, with this technique customers do not need to come to the institution's office to take care of opening an account. This is one of the considerations for customers in taking product funding at PT BPRS Lantabur Tebuireng because it provides convenience for customers, especially market traders. This research result of this study show that funding activities at PT BPRS Lantabur Tebuireng is quite effective in influencing customer preferences, the main and also supporting factors that become the reference for customers in making decisions to use funding products at PT BPRS Lantabur Tebuireng. These factors include service factors, convenience, according to Islamic law, promotion, culture, social and personal.